The Influence of Gadget Use on the Empathy of Junior High School Students in Palu City - Maabidah Maabidah; Nur Eka Wahyuningsih Riyadi; Ikhlas Rasido; Hasan Hasan (Journal of General Education and Humanities, 2026)
This study aims to determine the effect of gadget use on the empathy of junior high school students in Palu City. This study uses a quantitative descriptive approach with a cluster sampling technique. The population in this study comprises all students of Junior High School Model Terpadu Madani and Junior High School 19 Palu. Data were collected using a validated Likert-scale questionnaire on gadget use and empathy, both of which demonstrated good reliability (α = 0.914 and α = 0.885, respectively). Data analysis used descriptive statistics and simple linear regression using SPSS version 26. The results showed that 78.0% of students used gadgets highly, and 64.3% showed high empathy. The regression results showed a positive and significant effect of gadget use on empathy (t 3.653, p < 0.05), with a regression coefficient of 0.193. These results indicate that gadget use affects students' empathy, feelings, and understanding of the suffering of others who experience disasters through exposure to or visual content on gadgets. This fosters empathy as seen from large-scale online donations. Through emotional narratives and content, social awareness and empathy can be increased.